Вступ держав у Міжнародний валютний фонд - Шперун, Христина Всеволодівна; Шперун, Кристина Всеволодовна; Shperun, Kristina (Одеса : Юрид. л-ра, 2012)
The concept a n d types of m e m b e r s h i p in i n t e r n a t i o n a l o r g a n i z a t i o n s , i n c l u d i n g t h e I n t e r n a t i o n a l M o n e t a r y F u n d . The f e a t u r e s of t h e p r o c e d u r e of m e m b e r s h i p in t h e I n t e r n a t i o n a l M o n e t a r y F u n d a r e c h a r a c t e r i z e d . P a r t i c u l a r a t t e n t i o n is paid to t h e c h a r a c t e r i s t i c s of a p r e c e d e n t of g r a n t i n g associate m e m b e r s h i p in t h e o r g a n i z a t i o n of t h e USSR. A question of m e m b e r s h i p renewal a n d succession of m e m b e r s h i p in t h e I n t e r n a t i o n a l M o n e t a r y F u n d is separately analyzed.
Шперун Х. В. Вступ держав у Міжнародний валютний фонд / Х. В. Шперун // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 404-411.
Keywords: Міжнародний валютний фонд; членство; набуття членства; види членства; Международный валютный фонд; членство; виды членства; International Monetary Fund; membership; types of membership; I n t e r n a t i o n a l M o n e t a r y F u n d , m e m b e r s h i p , types of m e m b e r s h i p